Sound velocity and loss factor of polyurethane composites. Part II. - BANDERA, W.; PAWLACZYK, K. (Archives of Acoustics, 1991)
Elastic, non-foamed polyurethane compositions to be used as vibro-insulating materials have been developed. The compositions were prepared using poly(propylenoethers) of different molecular weights, toluyene diisocyanate and aluminum hydrate as the filling agent. The effect of the composition contents on viscoelastic properties that is, on sound velocity and loss factor has been determined. It has been found that various types of the filler permit to modify properties of composite and especially its stiffness and internal damping.